2015
DOI: 10.1002/mrm.25764
|View full text |Cite
|
Sign up to set email alerts
|

Velocity‐selective magnetization‐prepared non‐contrast‐enhanced cerebral MR angiography at 3 Tesla: Improved immunity to B0/B1 inhomogeneity

Abstract: Purpose To develop a Fourier-transform based velocity-selective (VS) pulse train that offers improved robustness to B0/B1 inhomogeneity for non-contrast-enhanced cerebral MR angiography (MRA) at 3T. Methods VS pulse train I and II with different saturation bands are proposed to incorporate paired and phase cycled refocusing pulses. Their sensitivity to B0/B1 inhomogeneity was estimated through simulation and compared with a single refocused VS pulse train. The implementation was compared to standard time-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 55 publications
1
102
0
Order By: Relevance
“…Velocity‐selective arterial spin labeling was found to produce nearly the same perfusion measurements using any of three orthogonal directions only if the cutoff velocity is reasonably small . Very recently, application of VS‐MRA for the cerebral arteries yielded only marginal difference in resultant angiograms obtained using VS preparations along each of three orthogonal directions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Velocity‐selective arterial spin labeling was found to produce nearly the same perfusion measurements using any of three orthogonal directions only if the cutoff velocity is reasonably small . Very recently, application of VS‐MRA for the cerebral arteries yielded only marginal difference in resultant angiograms obtained using VS preparations along each of three orthogonal directions .…”
Section: Discussionmentioning
confidence: 99%
“…The underlying rationale is similar to the one for the established T 2 preparation sequences in that the phase of the transverse magnetization made by the preceding rectangular RF pulse is barely changed by B 0 and B 1 offsets after multiple refocusing pulses weighted by MLEV phase cycling schemes . We consider double refocusing ( N refoc = 2) as well as quadruple refocusing ( N refoc = 4). Each velocity encoding step consists of a unipolar gradient N refoc refocusing pulses interleaved with ( N refoc − 1) bipolar gradients, each of which consists of two of the unipolar gradients, followed by another unipolar gradient with the opposite polarity to the initial unipolar gradient (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In this single‐refocused design, however, severe B 1 inhomogeneity causes distortion of velocity passband, which in turn results in signal loss in arterial blood. The latest studies on VS excitation pulse design have shown that multiple‐refocused designs substantially improve the immunity to both B 0 and B 1 offsets, being robust to wide ranges of the field errors …”
Section: Introductionmentioning
confidence: 99%
“…Overall, the B 1 error seemed to affect the diagnostic performance of VS‐MRA only marginally in this study performed at 1.5T, but might be a serious issue at 3T or higher fields. Recently, advanced versions of VS excitation pulse sequences have been developed that reduced the B 1 sensitivity through the use of two or four refocusing pulses and may be good alternatives at high field …”
Section: Discussionmentioning
confidence: 99%